Remote clinical training practice in the neurology internship during the COVID-19 pandemic - He, Miao; Tang, Xiang-qi; Zhang, Hai-nan; Luo, Ying-ying; Tang, Zhen-chu; Gao, Shu-guang (Medical education online, 2021)
Background: During the current COVID-19 pandemic, offline clinical education was mandated to suspend at the neurology department of many teaching hospitals globally, yet there is insufficient evidence regarding the preferred practice and methods for online neurology intern training course. Objective: The investigation aimed to examine whether the online neurology training course based on Small Private Online Course (SPOC) and blending learning mode can achieve a good effect and cater for interns from different medical programs and whether the learning group size affects the teaching effect. Design: The subjects were 92 students enrolled in the neurology internship at the Second Xiangya Hospital of China from 9 March to 9 August 2020. After completing the online course, the final scores and evaluation results were compared among different groups of interns, and their preference to distinct contents of the course was analyzed. Statistical analysis was performed using the SPSS program (version 22.0). Results: Our online course received consistent positive recognition from the interns. Ninety-nine percent of the interns recommended incorporating the online course into the conventional offline training program after the pandemic. There was no significant difference between interns from different programs concerning the final scores and course evaluation. A smaller learning group size (<15 students) could achieve a better teaching effect than a larger group size (p < 0.05). The interns preferred interactive discussions, and course contents that they can get practice and feedback from, rather than video watching and didactic lectures. Conclusions: The online neurology intern training course based on SPOC and blending learning mode is worthy of popularization in a large student base. The teaching effect of an online intern training program may be improved by limiting the group size to less than 15 students and encouraging more interactive discussion, more practice and feedback.